Eﬀectiveness of manual therapy and pain neuromuscular education on individuals with chronic non-speciﬁc low back pain: a narrative review and update of evidence-based physiotherapy practice - Kasimis, Konstantinos; Apostolou, Thomas; Kallistratos, Ilias; Lytras, Dimitrios; Iakovidis, Paris (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Chronic non-speciﬁc low back pain (CNLBP) is one of the main manifestations of musculoskeletal pain worldwide. A common practice in physiotherapy is the application of manual therapy (MT) techniques, while the value of patient education on pain neuroscience (PNE) as a complementary treatment in CNLBP management has also been highlighted in recent years. This narrative review investigated literature updates addressing the eﬀectiveness of combining MT and PNE in managing CNLBP.Methods. The PubMed, PEDro, and ScienceDirect databases were searched between November and December 2023 using diﬀerent combinations of keywords, including pain neuroscience education, pain neurophysiology education, manual therapy, and chronic low back pain. The search was ﬁltered for clinical studies published in the last decade.Results. Five randomised clinical trials with a total sample of 248 CNLBP patients met the inclusion criteria and were included in our review.Discussion. The results showed that adding PNE to an MT protocol further improved the pain intensity reduction, functional ability, pain-related psychological parameters, and quality of life of CNLBP patients compared to MT alone.Conclusions. The eﬃcacy of physiotherapy interventions increased when combining MT techniques with PNE. Consequently, MT interventions for CNSLBP should include PNE to obtain the optimum results in physiotherapy clinical practice.
Keywords: rehabilitation; chronic low back pain; pain neuromuscular education; manual therapy